Hyperlocal Multiplatform Approach for Cultural Preservation in the Galuh Prambanan TV Community - Rocky Prasetyo Jati (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This study explores the implementation of a hyperlocal and multiplatform media approach in cultural preservation within the digital era through a case study of Galuh Prambanan TV (GPTV) and Paguyuban Peduli Budaya Jawa (Bali-Buja) in Klaten, Central Java. Digital transformation has shifted society from passive consumers to active producers who shape cultural narratives through websites, social media, and video channels. Employing a qualitative ethnographic case study, this research examines how Javanese cultural values, community social structures, and digital technologies interact in the production and dissemination of cultural content. Data were collected through participatory observation, in-depth interviews, and digital documentation, and were analyzed thematically through data reduction, meaning categorization, and triangulation. The findings indicate that the hyperlocal multiplatform orchestration of GPTV–Bali-Buja has expanded the reach of traditional arts, strengthened community participation, and created digital archives serving as tools for education and cultural regeneration. The study concludes that successful cultural digitalization depends not only on technological capacity but also on local wisdom-based digital ethics and inclusive collaborative governance. Digitalization should be understood as a social practice that positions the community as the leading actor in cultural preservation, identity reinforcement, and creative-economy empowerment. Future research is recommended to examine the role of cooperative communication within cultural organizations, focusing on participatory leadership and collaborative communication patterns in managing community media.